(untitled) (Journal of the College of Basic Education, 2024)
The aim of the research is to identify: " effectiveness of the information gap strategy on the more achievement of students of the Department of Art in the Communication and Informatics" by verifying the following hypothesis: "There are no statistically significant differences at the level (0.05) between the average scores of the students of the experimental group who studied the communication and informatics according to the information gap strategy, and the average scores of the students who studied the same subject in the usual way in the achievement test." The current research was determined by fourth stage students of the Department of Art Education in the College of Basic Education, Al-Mustansiriya University, the morning study for the academic year (2021-2022). Their number is (160) male and female students, and his sample amounted to (30) male and female students for each group, the control and the experimental group, and they were chosen randomly The researcher two groups of research were rewarded in the variables (temporal, intelligence, previous information) as the content "Communication and Informatics Science" was identified and analyzed into (70) behavioural goals according to Bloom’s classification of the cognitive field ,To verify the hypothesis of the research, the researcher prepared an achievement test consisting of (30) items, The validity and reliability were verified, and then the data were processed statistically using (SPSS), as the results showed the superiority of the students of the experimental group over the students of the control group in the achievement test variable. The researcher recommended a number of recommendations, including the use of the "information gap strategy" in teaching the subject "Communication and Informatics" and suggested conducting other studies for different academic subjects and other academic stages to identify its impact on different variables.